2008
DOI: 10.1111/j.1365-2567.2007.02795.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide plays a key role in the platelet‐activating factor‐induced enhancement of resistance against systemic candidiasis

Abstract: SummaryPlatelet-activating factor (PAF) has been demonstrated to augment resistance against Candida albicans infection. In this study, the role of nitric oxide (NO) in PAF-induced resistance in the kidneys was investigated. Pretreatment of the C. albicans-infected mice with PAF resulted in strong expression of messenger RNA (mRNA) and the protein synthesis of inducible nitric oxide synthase (iNOS). These PAF effects were inhibited to a significant degree by pretreatment with the nuclear factor-jB inhibitor, py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A number of previous studies have shown that exogenous PAF C-16 can inhibit the growth of intracellular pathogens, including Leishmania donovani (Lonardoni et al, 2000), Leishmania braziliensis (Borges et al, 2017), Trypanosoma cruzi (Aliberti et al, 1999), and Candida albicans (Im et al, 1997;Kim et al, 2008) in vivo as well as in vitro. PAF C-16 induced growth inhibition of these intracellular pathogens was shown to be associated with an enhanced production of ROIs, RNIs, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies have shown that exogenous PAF C-16 can inhibit the growth of intracellular pathogens, including Leishmania donovani (Lonardoni et al, 2000), Leishmania braziliensis (Borges et al, 2017), Trypanosoma cruzi (Aliberti et al, 1999), and Candida albicans (Im et al, 1997;Kim et al, 2008) in vivo as well as in vitro. PAF C-16 induced growth inhibition of these intracellular pathogens was shown to be associated with an enhanced production of ROIs, RNIs, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous PAF C-16 has also been shown to inhibit the growth of intracellular pathogenic protozoans such as Leishmania and Trypanosoma inside human and mouse macrophages by causing the production of reactive oxygen and nitrogen species (Aliberti et al, 1999;Lonardoni et al, 2000;Borges et al, 2017). Similarly, administration of exogenous PAF C-16 in mice, infected with lethal doses of Candida albicans, reduced the number of pathogens and improved the survival via production of NO and TNF-α (Im et al, 1997;Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%